ALOE IRAFENSIS AN ENDEMIC PLANT OF YEMEN: PHYTOCHEMICAL SCREENING, ANTIBACTERIAL, ANTIOXIDANT, AND WOUND-HEALING ACTIVITIES - MOHARRAM, BUSHRA ABDULKARIM; AL-MAHBASHI, HASSAN M.; AL-MAQTARI, TAREQ; SAIF-ALI, RIYADH; AL-DOAISS, AMIN A. (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The objectives of the study were to determine the phytochemical constituents and assess the antibacterial, antioxidant, and wound-healing properties of the methanol extracts of Aloe irafensis. Methods: Methanol extracts of A. irafensis’s latex, gel, and green skin were screened for their phytochemical constituents. All three extracts were investigated regarding their antibacterial potential using disc diffusion and microdilution assays, and their antioxidant activity using 2,2-diphenyl-1- picrylhydrazyl free-radical scavenging assay. Histopathological study of wound healing area was performed for the latex extract in male albino rats. Results: The methanol extracts of A. irafensis revealed the presence of carbohydrates, steroids, phenols, tannins, and anthrones. The latex extract showed greater inhibition zones against Staphylococcus aureus and Pseudomonas aeruginosa (24 and 17 mm, respectively) and minimum inhibitory concentration values of 1.25 and 2.50 mg/ml, respectively. The latex extract showed the highest antioxidant activity (IC50 of 65.54 μg/ml), followed by green skin (IC50 of 89.48 μg/ml). The latex extract significantly accelerated the rate of wound healing in rats (p<0.01), compared to fucidin ointment, a reference control. Histological findings showed remarkably less scar width at wound closure site in the latex extract-treated wounds. Granulation tissue contained fewer inflammatory cells and more fibroblasts in wounds treated with the latex extract compared to those treated with the vehicle. Conclusion: A. irafensis latex extract is a potential source of bioactive compounds that can be used as antioxidant, antibacterial, and wound healing agents.